Organizing Expertise During a Crisis. France and Sweden in the Fight Against Covid-19 - Borraz Olivier; Jacobsson Bengt (Journal of Organizational Sociology)
In the fight against the Covid-19 virus, France and Sweden stood at opposing ends along a continuum: one country went for lockdowns; the other relied on voluntary measures. Both strategies were shaped by the governing structures in each country: in France complex and fragmented organizational arrangements focusing on health security, in Sweden a single dominant agency maintaining a broad public health perspective. Using concepts from organization theory – loose versus tight coupling and exploitation versus exploration – we show how the divergent strategies evolved in both countries. While loosely coupled organizational arrangements were rapidly tightened in Sweden, the system in France went in the opposite direction becoming loosely coupled. While the Swedish case was mainly one of exploitation of existing knowledge and expertise, more unchartered territories were explored in France. While alignment across actors in Sweden took place with one dominant agency in the center, alignment in France was related to actions of neighboring countries. Evidently, there was more than one way to fight the pandemic.